Maternal satisfaction on delivery care services and associated factors at public hospitals in eastern Ethiopia. Issue 2 (7th June 2022) - Kidane, Addisalem; Getachew, Tamirat; Mesfin, Firehiwot; Eyeberu, Addis; Dheresa, Merga
Abstract: Background: Maternal healthcare services satisfaction has been widely recognized as a critical indicator of quality in healthcare systems. Thus this study aimed to assess maternal satisfaction with delivery care services. Methods: An institutional-based cross-sectional study design was utilized among 400 randomly selected postnatal mothers from 1 to 30 February 2018. The data were entered into EpiData version 4.2.0 and computed using SPSS version 20. Bivariate and multivariate analyses were done using binary logistic regression to identify associations of factors. Results: A total of 400 participants were included, with a response rate of 98.8%. The overall delivery services satisfaction level of mothers was 80% (95% confidence interval [CI] 75.8 to 84.0). Delivery through caesarean section (adjusted odds ratio [AOR] 2.85 [95% CI 1.21 to 6.72]), privacy assured (AOR 3.73 [95% CI 1.79 to 7.75]), duration of labour (AOR 3.03 [95% CI 1.50 to 6.14]), waiting time (AOR 4.31 [95% CI 2.24 to 8.29]) and foetal outcome (AOR 4.33 [95% CI 1.94 to 9.66]) were associated with satisfaction with delivery care services. Conclusion: The study revealed that four-fifths of mothers were satisfied with the delivery care services provided in public hospitals. Much effort is needed from hospital administrators and health professionals to improve delivery services satisfaction by minimizing waiting time, maintaining privacy and securing waiting areas.